Architecture as Diplomatic Instrument? The Multi-Layered Meaning of the Belgian Embassy in New Delhi (1947–83). Issue 1 (6th October 2021) - De Maeyer, Bram; Floré, Fredie; Morel, Anne-Françoise
In recent decades, the topic of embassy architecture has increasingly drawn the attention of architectural historians. Whereas scholars have already shed light on the building policy of the United States, Great Britain and France, the architectural approach of small state actors such as Belgium has largely remained untouched. The Belgian purpose-built embassy (1980–83) in New Delhi was designed by the Indian artist-architect Satish Gujral. While the unusual design, with its references to indigenous Indian architecture, is often mentioned in the literature on Chanakyapuri, New Delhi's diplomatic neighbourhood, scholars have not addressed the Belgian rationale for constructing an embassy whose architecture paid more tribute to India than to Belgium. Examining the architectural and political meaning of this project in the context of both the receiving and the sending states, this article asks to what extent Belgium approached this diplomatic building project as an opportunity to cement its bilateral relationship with India. This embassy design was the result of not so much a well-considered building policy of Belgium but rather Gujral's personal stand with regard to the postmodernist debate in India's architecture scene at the time. In doing so, we make the case that purpose-built embassies – even the most expressive ones architecturally – are often more complex projects than closely monitored designs upon which governments project ideological and national visions.